A Literature Review of Teacher Strategies to Support Children with Selective Mutism in the Classroom - Hartati, Kurnia; Kurniati, Euis; Kurniawati, Leli (Aulad: Journal on Early Childhood, 2024)
Selective mutism (SM) presents unique challenges in the classroom, characterized by an inability to speak in specific social situations despite normal verbal abilities in other settings. This literature review aims to identify effective strategies for supporting children with SM. The objectives include understanding SM, educating the school community, and implementing individualized support strategies. The review employs a synthesis of current research to outline key approaches, emphasizing the importance of comprehensive awareness to avoid misconceptions and foster a supportive environment. Findings highlight the need for early identification, tailored interventions, and accommodating both verbal and non-verbal communication. Effective collaboration among teachers, parents, and therapists is essential for consistent support and progress. The review concludes that a holistic, empathetic approach combined with targeted strategies and community-wide education is critical for creating an inclusive classroom environment that supports the academic and social development of children with SM.